Economic and Environmental Pollutant Impact of Maternal–Fetal Telemedicine - Li Valverde, Valeria M.; Althaus, Elizabeth; Horton, Lauren; La Rosa, Mauricio F.; Haeri, Sina (American Journal of Perinatology, 2024)
The global issue of greenhouse gas emissions has significant implications for the environment and human health. Telemedicine provides a valuable tool for delivering health care while reducing gas emissions by limiting the need for patient travel. However, the environmental effects of telemedicine in high-risk pregnancy populations remain unassessed. The aim of this study was to estimate the economic and environmental impact of an outpatient teleMFM program.This retrospective cohort study examined all visits at three teleMFM clinics more than 90 miles away from the nearest in-person MFM office between October 1, 2021, and May 1, 2022. Travel distances and times were calculated for each appointment between the patient's home, telemedicine clinic, and nearest in-person clinics, using zip code data and Google Maps web-based map calculator tools. Travel cost savings and environmental impact were calculated by determining differences in mileage reimbursement rate and emissions between those incurred in attending telemedicine appointments and those that would have been incurred if in-person using inflation-adjusted Internal Revenue Service annual standard mileage reimbursement rate ($0.58 per mile), and the U.S. Environmental Protection Agency Office of Transportation and Air Quality's average annual emissions and fuel consumption for gasoline-fueled passenger vehicles.During the study period, a total number of 2,712 appointments were scheduled, of which 2,454 were kept (cancellations removed) and analyzed. Visiting a teleMFM clinic resulted in 204 miles, 200 minutes, and $118.32 saved per patient visit compared with visiting the nearest in-person clinic. Over a 7-month period, a total of 96.6 metric tons of emissions were saved.This study demonstrates the positive economic and environmental impact of teleMFM utilization in communities remote from in-person care. Given the contribution of greenhouse gas emissions to climate change, such findings may provide strategies for our specialty to make informed policy, advocacy, and business decisions.
Keywords: telemedicine; maternal–fetal medicine; climate change; environmental impact